2011
DOI: 10.1021/nn201391d
|View full text |Cite
|
Sign up to set email alerts
|

Sub-10 nm Nanofabrication via Nanoimprint Directed Self-Assembly of Block Copolymers

Abstract: Directed self-assembly (DSA) of block copolymers (BCPs), either by selective wetting of surface chemical prepatterns or by graphoepitaxial alignment with surface topography, has ushered in a new era for high-resolution nanopatterning. These pioneering approaches, while effective, require expensive and time-consuming lithographic patterning of each substrate to direct the assembly. To overcome this shortcoming, nanoimprint molds--attainable via low-cost optical lithography--were investigated for their potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 43 publications
1
125
0
Order By: Relevance
“…A typical example of this grafting method is a thermally activated reaction of the hydroxyl group at the chain end with the silanol group on the surface of the native oxide of the silicon wafer (Figure 2a) to form an ether bond [2,41]. Guo et al showed that a chain density (0-0.61 chains/nm 2 ) for low Mw polystyrene (PS) brush on a silicon substrate can be achieved by varying annealing temperature (110 to 150 °C) and time (s to days) [39] (Figure 2b).…”
Section: Solid State Graftingmentioning
confidence: 99%
“…A typical example of this grafting method is a thermally activated reaction of the hydroxyl group at the chain end with the silanol group on the surface of the native oxide of the silicon wafer (Figure 2a) to form an ether bond [2,41]. Guo et al showed that a chain density (0-0.61 chains/nm 2 ) for low Mw polystyrene (PS) brush on a silicon substrate can be achieved by varying annealing temperature (110 to 150 °C) and time (s to days) [39] (Figure 2b).…”
Section: Solid State Graftingmentioning
confidence: 99%
“…The surface morphologies of annealed films were observed in dynamic force mode using an atomic force microscope (SII S-image) and cantilevers (Olympus OMCL-AC200TS-R3). PS-OH with Mn = 3,200 g mol -1 was purchased from Polymer Source Inc. to prepare silicon substrates modified with PS-OH [7]. A toluene solution containing 1.0 wt% PS-OH was spincoated onto a bare silicon substrate at 3,000 rpm for 30 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Directed self-assembly (DSA) using thin films of block copolymers (BCPs) is one of promising lithographic processes to miniaturize electronic components less than 20 nm, because BCPs self-assemble into periodic nanostructures at large areas [1][2][3][4][5][6][7]. The relationships between chemical and topological guiding pattern and assembled BCP morphology have been investigated [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Graphoepitaxy alone can also unidirectionally align line patterns and organize spherical domains. Use of faceted surfaces [95] and 1D groove templates [52], due to entropic effects, as well as nanoimprint lithography [96,97] (NIL), due to surface effects on the vertical groove walls, are efficient techniques to orient BCP nanostructures without requiring macromolecule-scale prior patterning. In the case of reconstructed sapphire surfaces, the atomic crystalline ordering of the substrate can be transferred, over multiple length scales, to the block copolymer microdomains, via facets regular pattern.…”
Section: In-plane Degeneracy and Single-grain Formationmentioning
confidence: 99%